Hubungan Pengetahuan Dengan Kepatuhan Minum Obat Hipertensi Di Wilayah Kerja Puskesmas Wonogiri - Rice Hernanda; Ardinata Ardinata; Septiara Dwi Enggani (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
In 2020, non-communicable diseases (NCDs) accounted for 73% of global causes of death, claiming the lives of 36 million people annually. The rising rates of morbidity and mortality are influenced by hypertension. One of the most prevalent cardiovascular disorders in the world today is hypertension.The research objective was to determine the correlation between knowledge with compliance with taking medication for hypertension sufferers at the Wonogiri Public Health Center in North Lampung Regency. This research type is quantitative using a cross-sectional design with a population of 471 people. The sampling technique used purposive sampling of 83 respondents. The statistical tests used are Gamma and Logistic Regression. The study findings demonstrated a significant correlation between knowledge and hypertension patients' compliance to taking their medications (p-value=0.000).